Antibiotics Post-Appendectomy in Pediatric Patients : A Literature Review Leading to Proposition of a New Treatment Protocol - Goovaerts, Charlotte; Miserez, Marc; van Hoeve, Karen; Hoffman, Ilse (Belgian Journal of Paediatrics, 2024)
Although acute appendicitis is a common occurrence in the pediatric population, there is still considerable debate surrounding the optimal postoperative antibiotic treatment. Currently, there is a lack of a clear, evidence-based protocol for postoperative treatment. The objective of this review is to develop a protocol for postoperative antibiotic treatment in children with acute appendicitis. By introducing this protocol, we aim to establish a more straightforward policy and avoid overtreatment with antibiotics.